The neurophysiological correlates of cognitive functions during methadone and buprenorphine maintenance treatment: The ERP study - Silvana Markovska-Simoska; Liljana Ignjatova; Gordana Kiteva Trenchevska; Nada Pop-Jordanova (AU-CNS, 2021)
Background. The treatment of opioid dependence with methadone and buprenorphine is equally effective with either of the two drugs, in terms of discontinuation and retention in treatment. Buprenorphine, unlike methadone, is, however, renowned for being a drug that gives a "clear head", which is encouraging for those who are students, or who are, in any case, engaged in intellectual work. Aim. The aim of this study has been to determine if there is a difference in the neurophysiological correlates of cognitive functions in individuals treated with methadone (MMT) versus those treated with buprenorphine (BMT). Methods. The study includes 10 participants belonging to the MMT group and 10 others involved in the BMT group; both these study groups were compared with the control group after matching had been carried out for age and gender. Brain activity was recorded with the QEEG Mitsar system while study participants were performing two neuropsychological tasks. The VCPT and ECPT as modifications of the Go/NoGo paradigm were applied in order to obtain cognitive event-related potentials (ERPs) as indexes of executive functions. Besides the behavioural parameters of test performance, amplitude and latency of CNV, Cue P3, P3 Go, P3NoGo, N2Go and N2 NoGo were explored at Fz, Cz and Pz, reflecting different stages of information processing. Results. The MMT group showed longer latencies of the ERP components, and the BMT participants showed slightly better results than those of the MMT group. Still, most of the parameters did not differ significantly from those of the control group. Behavioural parameters showed significantly higher values for variables in the results for reaction time and the number of errors of omission and commission found in the competing MMT vs BMT groups, as well as the control group. Conclusions. Neurophysiological evidence suggests that methadone and buprenorphine both have positive effects on neurophysiological functions, as fewer abnormalities were found in MMT or BMT patients than in healthy controls. It has been shown that the sensitivity and specificity of detecting drug effects increase significantly when adding neurophysiological measures to task performance.
Keywords: event-related potentials; go/NoGo task; methadone; buprenorphine; maintenance treatment